Congenital vascular malformations - Schlembach, D. (Phlebologie, 2016)
Congenital vascular anomalies may occur at any anatomical region, but genital vascular anomalies in women are rare findings. Therefore the majority of the problems in pregnancy are due to secondary complications of vascular anomalies (especially in syndromes). Proper knowledge of these disorders and the necessities in diagnosis and management is essential.
Keywords: Congenital vascular malformation; genital; Klippel-Trénaunay syndrome; hereditary haemorrhagic telangiectasia